1940
DOI: 10.3733/hilg.v13n04p141
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate concentration and ion balance in relation to citrus nutrition

Abstract: Introduction. Experimental procedure Preliminary experiments. Sand-culture experiment Automatically operated sand cultures Composition of nutrient solutions. Control of nutrient concentration Methods of analysis. Nitrogen. Phosphorus. Sulfur Chlorine Calcium, magnesium, and potassium Results. The effects of high chloride and high sulfate Calcium-potassium relations Nitrogen-phosphorus relations The effect of increased nitrate on chloride and sulfate absorption Leaf color and nitrogen content as an index of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1942
1942
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…However, very few reports have been published on N fertilization of citrus nursery plants. Chapman and Liebig (1937;1940) found that sweet orange seedling growth with N at 0.14, 0.7, 1.4, or 840 mg•liter -1 was markedly reduced compared to plants grown at 70 or 420 mg•liter -1 . Only slightly less growth was achieved at 7 mg N/liter, and the authors suggested that the optimal solution N concentration was ≈10 mg•liter -1 .…”
mentioning
confidence: 99%
“…However, very few reports have been published on N fertilization of citrus nursery plants. Chapman and Liebig (1937;1940) found that sweet orange seedling growth with N at 0.14, 0.7, 1.4, or 840 mg•liter -1 was markedly reduced compared to plants grown at 70 or 420 mg•liter -1 . Only slightly less growth was achieved at 7 mg N/liter, and the authors suggested that the optimal solution N concentration was ≈10 mg•liter -1 .…”
mentioning
confidence: 99%
“…Although these data do not indicate, save by inference, what periods of the year are most vital as regards the nutrient supply of nitrogen, they do show clearly the seasons of maximum and minimum absorption and afford information of interest as bearing on the relation of nitrate absorption to temperature conditions, periods of root and top growth, and transpiration. Data concerning total leaf number and leaf area and observations on their seasonal fluctuations and relations are include'd in this report. To the knowledge of the authors, no studies of like nature have been recorded for citrus, although with reference to the seasonal requirements of these trees, CAMERON (1), CAMERON and APPLEMAN (3, 4), and CAMERON, APPLEMAN, and BIALOGLOWSKI (6), from analyses of leaves, flowers, and young fruit from field trees, have indicated the importance of the nitrogen supply within the tree prior to and during the period of blossoming, spring growth, and fruit setting. These investigators and, more recently, MARTIN (10), and HILGEMAN, SMITH, and DRAPER (7) A record of the amounts of distilled water added during the week to compensate for transpiration and the small loss from evaporation was also kept.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also showed that optimal growth under solution culture occurred at N concentrations between 0.52 and 0.7 mmol compared to 1-1.5 mmol for sand cultures (Chapman and Liebig 1941 ;Maust and Williamson 1994 ) . It could be argued that the intense mixing of an aerated solution culture system facilitates more ef fi cient nitrate uptake especially at low N concentrations.…”
Section: Soil Water Status and Nutrient Uptakementioning
confidence: 98%
“…Although concentrations of 200-400 mg N mg N L −1 are commonly used for fertigation of citrus grown in a potting medium, optimal growth could be attained with soil N concentrations of 15-20 mg N L −1 for an inert sand (Maust and Williamson 1994 ) and 10 mg N L −1 with solution culture (Chapman and Liebig 1941 ) . To date, most uptake studies for citrus focused on growth response to N supply (Chapman and Liebig 1941 ;Lea-Cox and Syvertsen 1996 ;Dou and Alva 1998 ) , long-term N uptake, and/or N partitioning within the plant (Legaz and Primo-Millo 1988 ;Syvertsen 1993, 1996 ) . Although plant growth response to N supply has been studied extensively, the physiological basis for improving nutrient uptake ef fi ciency (NUE) in crops remains poorly understood (Rufty et al 1990 ) .…”
Section: Uptake Mechanismsmentioning
confidence: 99%